Xenophobia In South Africa and the Realities of Actualizing SDG 8 - Onor, Kester Chuwuma (Universitas Medan Area, 2024)
This study dwells on xenophobia and the realities of actualizing the United Nations (UN) Sustainable Development Goal (SDG) eight in South Africa. It argues that since the emergence of Millennium Development Goals (MDGs) in 2000, which transited to Sustainable Development Goals (SDGs) in 2015, there has been a proliferation of literature from scholars of diverse disciplinary orientations. However, none of these studies deal with the phenomenon of xenophobia as a milestone for the attainment of the SDGs in South Africa. This paper, therefore, serves as an intervention to discuss how xenophobia affects the realization/ actualization of the UN’s SDG eight in the area under consideration. Using extant literature and the rational choice theory, it affirms that without peace and partnership with other countries, it would be very difficult for South Africa to attain the UN SDGs it envisages to achieve. To be focused and in-depth in the analysis of the phenomena under consideration the study centers exclusively on the UN SDG eight (even though there are seventeen SDGs of the UN) which hinges on decent work and economic growth. The evidence thrown up led to the major conclusion that the persistent xenophobic attacks and the resultant massive destruction of lives and businesses of foreigners, South Africa’s quest for the full-fledged realization of United Nations (UN) Sustainable Development Goal eight would remain mere paperwork. Given the increasing prevalence of xenophobic attacks in the study area, the paper suggests, among others, the building of meaningful, lasting, and effective partnerships. This entails that xenophobia in the country will be nipped in the bud.